(untitled) (World Economics and Finance Bulletin, 2023)
The aim of the research is to shed light on the impact of economic corruption on development in general and on Iraq in particular, in order to address weaknesses and provide a set of solutions to confront this scourge that resulted in a significant backwardness in development. Economic conditions that threatened economic stability, so the research problem was summarized by the impact of corruption. On the comprehensive development in Iraq as a result of wasting and wasting economic resources, so the importance of the research was manifested in the fact that it deals with a serious negative economic phenomenon that left devastating effects on the Iraqi economy, and for this purpose the descriptive analytical approach was used, and thus the study came with many results, and in light of that. Appropriate recommendations have been made